Basic psychological need satisfaction and frustration in major depressive disorder - Pietrek, Anou; Kangas, Maria; Kliegl, Reinhold; Rapp, Michael A.; Heinzel, Stephan; van der Kaap-Deeder, Jolene; Heissel, Andreas (Frontiers in Psychiatry, 2022)
Basic Psychological Needs Theory postulates that a social environment that satisfies individuals’ three basic psychological needs for autonomy, competence, and relatedness leads to optimal growth and well-being. On the other hand, the frustration of these needs is associated with ill-being and depressive symptoms foremost investigated in non-clinical samples; yet there is a paucity of research on need frustration in clinical samples. Survey data were compared between adult individuals with Major Depressive Disorder (MDD; n = 115; 48.69% female; 38.46 years, SD = 10.46) with those of a non-depressed comparison sample (n = 201; 53.23% female; 30.16 years, SD = 12.81). Need profiles were examined with a Linear Mixed Model (LMM). Individuals with depression reported higher levels of frustration and lower levels of satisfaction in relation to the three basic psychological needs when compared to non-depressed adults. The difference between depressed and non-depressed groups was significantly larger for frustration than satisfaction regarding the needs for relatedness and competence. LMM correlation parameters confirmed the expected positive correlation between the three needs. This is the first study showing substantial differences in need-based experiences between depressed and non-depressed adults. The results confirm basic assumptions of the Self-Determination Theory and have preliminary implications in tailoring therapy for depression.